Heavenly tyrant ebook - Zhao, Xiran Jay (Iron Widow, 2024)
Instant #1 New York Times Bestseller CBC bestseller USA Today bestseller Zetian must balance dangerous politics with a new quest for vengeance in the sequel to the #1 New York Times bestseller Iron Widow . Pacific Rim meets The Handmaid's Tale in this blend of Chinese history and mecha science fiction for YA readers. After suffering devastating loss and making drastic decisions, Zetian finds herself on the seat of power in Huaxia, but she has also learned that her world is not as it seems. Revelations about an enemy who dangles one of her loved ones as a hostage force Zetian to share power with a dangerous man she cannot simply depose. Despite their mutual dislike and distrust, the two must work together to take down their common enemy and stoke a revolution against the systems of exploitation that plague their world. However, power is not so easy to wield once seized, and a revolution is not so easy to control once unleashed. As Huaxia’s former elites strike back and the common people’s fervor for justice turns bloody and paranoid, can Zetian remain a fair and just ruler? Or will she be forced to rely on fear and violence and succumb to her darker instincts in her quest for vengeance and liberation?